2021
DOI: 10.3389/fonc.2021.669195
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Atezolizumab Versus Chemotherapy as First-Line Treatment for Metastatic Non-Small-Cell Lung Cancer With Different PD-L1 Expression Status

Abstract: BackgroundAtezolizumab could significantly improve clinical outcomes and was associated with less toxicity compared with chemotherapy as the first-line treatment of PD-L1-selected patients with EGFR and ALK wild-type metastatic non-small-cell lung cancer (NSCLC). However, the economic outcomes remain unclear yet in China. This study aimed to investigate the cost-effectiveness of atezolizumab versus chemotherapy as first-line therapy for metastatic NSCLC with different PD-L1 expression status from the Chinese h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…First, the KM survival curve was obtained from the IMpower010 trial to extrapolate the longterm clinical effect of the drug by fitting a parameter function, and the extrapolation time exceeded the real follow-up time of the trial, incurring inevitable limitations and perhaps lead to deviations between the model results and the actual situation. Second, some key clinical costs were derived from the literature rather than survey data from this study (34)(35)(36)(37)(38)(39)(40), such as the subsequent treatment cost of PD, considering only the cost of grade III/IV adverse events reported by ≄ 1% of patients in the IMpower010 trial, this may lead to inaccurate estimates of AE costs. By changing the model input within a certain range to run the probability sensitivity analysis, it was found that ICER was not sensitive to AE cost.…”
Section: Discussionmentioning
confidence: 99%
“…First, the KM survival curve was obtained from the IMpower010 trial to extrapolate the longterm clinical effect of the drug by fitting a parameter function, and the extrapolation time exceeded the real follow-up time of the trial, incurring inevitable limitations and perhaps lead to deviations between the model results and the actual situation. Second, some key clinical costs were derived from the literature rather than survey data from this study (34)(35)(36)(37)(38)(39)(40), such as the subsequent treatment cost of PD, considering only the cost of grade III/IV adverse events reported by ≄ 1% of patients in the IMpower010 trial, this may lead to inaccurate estimates of AE costs. By changing the model input within a certain range to run the probability sensitivity analysis, it was found that ICER was not sensitive to AE cost.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with no tumor profiling in patients with metastatic lung adenocarcinoma, tumor profiling improves quality-adjusted survival, but it is not cost-effective, especially in the wild type and where there is a rare mutation [17]. This situation could be improved by expanding the coverage of medical insurance and supplementary commercial insurance for targeted drugs and immunotherapy [18].…”
Section: Achievements and Social Benefitsmentioning
confidence: 99%
“…After disease progression, all patients had the same opportunity to receive second-line treatment according to the guidelines of the Chinese Society of Clinical Oncology (CSCO) for oesophageal cancer (2021) [20] and the ORIENT-15 data [10]. All costs were obtained from local hospitals and previously published literature [21][22][23][24][25][26][27][28]. All costs were adjusted to US dollars in 2021 ($1 = 6.45…”
Section: Cost and Utility Estimatesmentioning
confidence: 99%
“…The utility values for health states in the model were derived from a worldwide, randomized, double-blind phase III clinical study that recruited patients with advanced gastric cancer or gastroesophageal junction adenocarcinoma [22,29]. The disutility caused by adverse events was also considered in this cost-effectiveness analysis [21,27]. The key model parameters are shown in Table 2.…”
Section: Cost and Utility Estimatesmentioning
confidence: 99%